Unilateral Uterine Artery Embolization Therapy For Secondary Postpartum Hemorrhage In Pseudoaneurysma Of The Sinistra Uterinary Artery Post-Cesarean Section - Arghya Wicaksana; Agung Setiawan (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2022)
Introduction: Uterine artery pseudoaneurysm is one of the rare malformations of uterine blood vessels due to incomplete closure of the torn uterine artery wall. This condition accounts for about 3% of postpartum hemorrhage cases that could be life-threatening. Transcatheter arterial embolization has recently emerged as a safe and highly effective alternative treatment. Case Presentation: A 30-year-old woman complained of abdominal pain accompanied by a large amount of blood from the birth canal, which was felt on the 28th day after a cesarean section. The patient underwent laparotomy and had grade III intra-abdominal adhesions. On CT-Angiography investigation, we found saccular type aneurysm in the left uterine artery, hematometra, and fluid collection on the right side of the periuterine, multiple paraaortic lymphadenopathies, hepatomegaly, and left adnexal cyst. With the pseudoaneurysm, the patient was planned to undergo uterine artery embolization. The patient was discarded. During follow-up, results of CT-scan pelvic angiography include dilated and convoluted right uterine artery. Conclusion: In this case report, uterine artery embolization (UAE) was performed; this procedure was chosen because the effectiveness of embolization was 97% and could maintain the desire for future pregnancies. The fertility prognosis in this case report was quite good after unilateral uterine artery embolization was performed concerning regular menstrual cycles.